Bookmark. Ancient Gems, Finger Rings and Seal Boxes from Caesarea Maritima. The Hendler Collection - Amorai-Stark, Shua; Hershkovitz, Malka (Journal of Hellenistic Pottery and Material Culture, 2018)
To date, this impressive publication is the only book dealing with ancient gems, finger rings and seal boxes from an ancient site in Roman-Byzantine Palestine. It presents the private Collection of Johanan Hendler who gathered the objects together with his sons between 1950 and the early 1970’s. The Collection was authorized for publication by the Israel Antiquities Authority.